Cavity-enhanced high harmonic generation for extreme ultraviolet time- and angle-resolved photoemission spectroscopy - Mills, A. K.; Zhdanovich, Sergey; Na, M. X.; Boschini, Fabio; Razzoli, E.; Michiardi, M.; Sheyerman, Alexander; Schneider, Michael; Hammond, T. J.; Suess, V.; Felser, Claudia; Damascelli, Andrea; et al. (Review of Scientific Instruments, 2019)
With its direct correspondence to electronic structure, angle-resolved photoemission spectroscopy (ARPES) is a ubiquitous tool for the study of solids. When extended to the temporal domain, time-resolved (TR)-ARPES offers the potential to move beyond equilibrium properties, exploring both the unoccupied electronic structure as well as its dynamical response under ultrafast perturbation. Historically, ultrafast extreme ultraviolet sources employing high-order harmonic generation (HHG) have required compromises that make it challenging to achieve a high energy resolution - which is highly desirable for many TR-ARPES studies - while producing high photon energies and a high photon flux. We address this challenge by performing HHG inside a femtosecond enhancement cavity, realizing a practical source for TR-ARPES that achieves a flux of over 1011 photons/s delivered to the sample, operates over a range of 8-40 eV with a repetition rate of 60 MHz. This source enables TR-ARPES studies with a temporal and energy resolution of 190 fs and 22 meV, respectively. To characterize the system, we perform ARPES measurements of polycrystalline Au and MoTe2, as well as TR-ARPES studies on graphite.
CRIS-Team Scopus Importer:2022-04-14